2021
DOI: 10.1111/geb.13433
|View full text |Cite
|
Sign up to set email alerts
|

Responses of soil bacterial community structure and function to dry–wet cycles more stable in paddy than in dryland agricultural ecosystems

Abstract: Aim: Climate change is the foremost cause of terrestrial biodiversity decline, but the microbial communities from different habitats do not respond equally to environmental change. However, our understanding of the response patterns of microbial diversity to climate change remains limited in distinct agriculture ecosystems across large spatial scales. Here, we explore the response patterns of soil bacterial community structure and function to dry-wet cycles in dryland (maize) and paddy (rice) agricultural ecos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…In particular, we revealed that community resistance exhibited positive effect on ecosystem multifunctionality, indicating the importance of community resistance in maintaining ecosystem functions in agricultural ecosystems. This could be supported that the tolerant microbial taxa were closely related to nutrient cycling under disturbances (Jiao, Du, et al, 2019; Qi et al, 2021). In addition, key soil taxa had a positive effect on the resistance of multiple ecosystem functions related to soil carbon, nitrogen and phosphorus cycling following simulated climate change (Delgado‐Baquerizo et al, 2017).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In particular, we revealed that community resistance exhibited positive effect on ecosystem multifunctionality, indicating the importance of community resistance in maintaining ecosystem functions in agricultural ecosystems. This could be supported that the tolerant microbial taxa were closely related to nutrient cycling under disturbances (Jiao, Du, et al, 2019; Qi et al, 2021). In addition, key soil taxa had a positive effect on the resistance of multiple ecosystem functions related to soil carbon, nitrogen and phosphorus cycling following simulated climate change (Delgado‐Baquerizo et al, 2017).…”
Section: Discussionmentioning
confidence: 78%
“…In addition, water-saturated ecosystems display a complex and highly connected distribution of water in soil pores (Chen et al, 2021), which create more open environments for soil microbes to be easily influenced by environmental changes. A recent sibling study demonstrated that responses of soil bacterial community structure and function to dry-wet cycles were more stable in paddy than in dryland ecosystems (Qi et al, 2021). Given that multiple organism groups (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to maize soils, paddy fields are subject to more agricultural disturbances, such as experiencing more human-driven physical practices and suffering larger fluctuations in soil moisture. Soil moisture is one of major drivers on microbial communities structure 39 , 40 , and drought-rewetting events might attenuate the direct contribution of micronutrients on soil microbial communities by directionally promoting moisture-insensitive taxa 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…We focused on the dynamic recovery of eukaryotic and bacterial biodiversity (alpha, beta and network) and ecosystem functions (ecosystem metabolism and denitrification) after different drought durations, with the prime focus on analysing the relative importance of biodiversity on ecosystem functions by partial least squares path models (PLS‐PMs). Based on the research of Sabater et al (2016) that eukaryotes and bacteria in biofilms have different responses to dry and wet alternations (Qi et al, 2022), we hypothesized the following: (i) bacterial biodiversity may be more sensitive to drought duration than eukaryotic and (ii) the intensification of drought will significantly affect biodiversity and ecological function (Migliavacca et al, 2021), and the relative importance of biodiversity on ecosystem functions may change after different drought durations.…”
Section: Introductionmentioning
confidence: 99%